The Phenotypic and Transcriptomic Response of the Caenorhabditis elegans Nematode to Background and Below-Background Radiation Levels - Van Voorhies, Wayne A.; Castillo, Hugo A.; Thawng, Cung N.; Smith, Geoffrey B. (Frontiers in Public Health, 2020)
Studies of the biological effects of low-level and below-background radiation are important in understanding the potential effects of radiation exposure in humans. To study this issue we exposed the nematode Caenorhabditis elegans to average background and below-background radiation levels. Two experiments were carried-out in the underground radiation biology laboratory at the Waste Isolation Pilot Plant (WIPP) in New Mexico USA. The first experiment used naïve nematodes with data collected within 1 week of being placed underground. The second experiment used worms that were incubated for 8 months underground at below background radiation levels. Nematode eggs were placed in two incubators, one at low radiation (ca.15.6 nGy/hr) and one supplemented with 2 kg of natural KCl (ca. 67.4 nGy/hr). Phenotypic variables measured were: (1) egg hatching success (2) body size from larval development to adulthood, (3) developmental time from egg to egg laying adult, and (4) egg laying rate of young adult worms. Transcriptome analysis was performed on the first experiment on 72 h old adult worms. Within 72 h of being underground, there was a trend of increased egg-laying rate in the below-background radiation treatment. This trend became statistically significant in the group of worms exposed to below-background radiation for 8 months. Worms raised for 8 months in these shielded conditions also had significantly faster growth rates during larval development. Transcriptome analyses of 72-h old naïve nematode RNA showed significant differential expression of genes coding for sperm-related proteins and collagen production. In the below-background radiation group, the genes for major sperm protein (msp, 42% of total genes) and sperm-related proteins (7.5%) represented 49.5% of the total genes significantly up-regulated, while the majority of down-regulated genes were collagen (col, 37%) or cuticle-related (28%) genes. RT-qPCR analysis of target genes confirmed transcriptomic data. These results demonstrate that exposure to below-background radiation rapidly induces phenotypic and transcriptomic changes in C. elegans within 72 h of being brought underground.